Edukasi Perencanaan Keuangan dan Investasi Terhadap Perilaku Keuangan Gen Z pada Mahasiswa Semester 4 Ekonomi Syariah STAI Sangatta Kutai Timur - Totok Adhi Prasetyo; Alyani; Muhammad Irsyad Al-banjari; Anggun Citra Lukmania; Adna Fika Abidah Ardeliana (PT. Pustaka Andil Lestari, 2024)
Explore the influence of understanding financial planning and investment on the financial behaviour of Sharia Economics students. This study is to determine the effect of financial planning and investment on financial behaviour in 4B semester students of Sharia Economics at the College of Islamic Religion (STAI) Sangatta East Kutai. By using quantitative descriptive method. This study involved 17 student respondents selected through purposing sampling. Data were collected through questionnaires that had been preceded by financial planning and investment education. Descriptive statistical analysis of data quality test, classical assumption test, multiple linear regression test, and coefficient of determination were processed with the help of SPSS Version 12.0. delivering on significant findings. financial planning education and investment proven have a positive and significant influence on the financial behaviour of students. Keywords: Financial Planning education, Investment, Gen Z students and Financial Behaviour